What Explains Natives and Sojourners Preventive Health Behavior in a Pandemic: Role of Media and Scientific Self-Efficacy - Keren, Fang; Siddiquei, Ahmad Nabeel; Anwar, Muhammad Azfar; Asmi, Fahad; Ye, Qing (Frontiers in Psychology, 2021)
The COVID-19 pandemic triggered a severe global public health emergency. The current research investigated and compared “Natives and Sojourners” health-protective behaviour in Mainland China during the pandemic. We adopted a unified view to propose our theoretical model by adapting the Health Belief Model (HBM) and Institutional Theory (IT). The data obtained through an online survey questionnaire from 435 respondents during the second and third quarters of 2020 were analysed. Structural Equation Model (SEM) was used to empirically analyse the proposed model. The media self-efficacy, scientific self-efficacy, perceived health risks and the perceived benefits of being protected have positive and significant effects on the definition of health-protective behavioural intentions among natives and sojourners in mainland China. Media and scientific self-efficacy can play a strategic role in formulating public health-protective behaviour. The current research recommends effective communication with sojourners during a crisis for them to be a part of the national crisis management plan (i.e. infectious disease).